2020
DOI: 10.3390/su12041289
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating a Green Agri-Food Supply Chain with Revenue-Sharing Contracts Considering Retailers’ Green Marketing Efforts

Abstract: Serious environmental issues have drawn the attention of the agricultural sector. Consumers’ concerns about their personal health and food safety have stimulated the demand for green agri-food, which has also made it important to focus on the green agri-food supply chain to improve the food quality and reduce the associated environmental concerns. This paper discusses coordination issues of the green agri-food supply chain under the background of farmers’ green farming and retailers’ green marketing, and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 50 publications
(59 reference statements)
0
24
0
Order By: Relevance
“…Some studies focused on GSCM under the capital constraint without considering green marketing efforts [5,48,52,53]. Meanwhile, some other studies discussed green marketing efforts without paying attention to retailers' capital constraints [9,16]. This paper's research contents are compared with the existing research results, as shown in Table 1.…”
Section: Gsc Financing With Capital Constraintmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies focused on GSCM under the capital constraint without considering green marketing efforts [5,48,52,53]. Meanwhile, some other studies discussed green marketing efforts without paying attention to retailers' capital constraints [9,16]. This paper's research contents are compared with the existing research results, as shown in Table 1.…”
Section: Gsc Financing With Capital Constraintmentioning
confidence: 99%
“…Green marketing originates from developed countries' environmental protection regulations and policies in Europe and America for various industries. At present, it has been confirmed that green marketing plays a crucial role in promoting green products to achieve green supply chain (GSC) sustainability [9]. From the perspective of environmental 1.…”
Section: Introductionmentioning
confidence: 97%
“…In this paper, we first constructed Stackelberg game models for a low-carbon supply chain, which consists of one manufacturer (leader) and one capital-constrained retailer(follower), similar to the application of this model in previous studies [ 37 , 38 , 39 , 40 ]. Currently, the manufacturer is adopting innovative and environmentally friendly technologies to produce low-carbon products to reduce carbon emissions, the retailer is ordering low-carbon products and promoting them in the market, and consumers are becoming more environmentally aware and they prefer low-carbon products.…”
Section: Problem Description and Assumptionsmentioning
confidence: 99%
“…This is a two-echelon Stackelberg problem and we solve it by the inverse induction method, like the research conducted by [ 6 , 39 ]. First, the manufacturer uses the retailer’s optimal response function to determine the wholesale price and level of carbon emissions reduction efforts; then, the retailer determines the retail price according to the manufacturer’s decision.…”
Section: Low-carbon Supply Chain Financing Strategiesmentioning
confidence: 99%
“…As an important indicator of the quality of fresh produce, freshness preservation also influences the quality of agri-foods and revenue of participants [33]. When consumers have increased sensitivity in high-level green agri-foods, members of the supply chain are willing to participate in coordination [34]. These studies mostly aim at maximizing the benefit of the members of the agri-food supply chain and obtaining optimal pricing, investment, and revenue coordination mechanisms [35][36][37].…”
Section: Relevant Literature Reviewmentioning
confidence: 99%